2019
DOI: 10.17576/mh.2019.1401.05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Simulation in Malaysian Healthcare Education and Research (ISIM-HERE): A Two- Decade Experience

Abstract: Penggunaan simulasi sebagai metodologi pengajaran di institusi kesihatan telah berada di Malaysia semenjak dua dekad. Kajian ini bertujuan untuk menilai kesan simulasi pada senario semasa dan penggunaan di Institusi Pendidikan Kesihatan (AHIs) di Malaysia. Kami telah menjalankan soal selidik ke atas semua populasi AHIs di Malaysia termasuk awam dan swasta. Kami menjalankan soal selidik secara atas talian diikuti dengan temubual secara bersemuka dan menilai jumlah institusi yang menggunakan simulasi, tempoh pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Incorporating role-plays, comprehensive feedback, and personalized suggestion is another factor in the significant improvement of attending Online AdCARE ( 64 ). This is consistent with another study, that has shown the added value of these hands-on experiences as the key factor that results in the significant improvement of the SE domain especially in endorsing a positive attitude, making a suicide risk assessment, developing treatment plans, and establishing rapport ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating role-plays, comprehensive feedback, and personalized suggestion is another factor in the significant improvement of attending Online AdCARE ( 64 ). This is consistent with another study, that has shown the added value of these hands-on experiences as the key factor that results in the significant improvement of the SE domain especially in endorsing a positive attitude, making a suicide risk assessment, developing treatment plans, and establishing rapport ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation has been in use as a teaching tool in medical schools in Malaysia for more than 20 years. About three quarters of the teaching institutions have dedicated support staff to manage the simulations centres according to one study (Mohd Saiboon, 2019).…”
Section: Simulation Training In Malaysiamentioning
confidence: 99%
“…Healthcare educators need to consider several factors when preparing to utilise technology: the first language of their learners and the availability of appropriate resources (Bala Krishnian et al, 2016;Duff et al, 2016); the learners' computer skills (Duff et al, 2016); the availability of technical support and how the various technologies can be integrated into the institution's virtual learning environment (Masters et al, 2016).…”
Section: Preparing To Use Technologymentioning
confidence: 99%
“…The immediate feedback provided through the two-way clicker technology can also be beneficial for assessing the learners' understanding (De Gagne, 2011). Video-assisted learning (which can be facilitated either in the classroom or via e-learning) has been shown to increase the confidence of paramedics when learning emergency skills and encourage them to undertake independent learning (Bala Krishnian et al, 2016).…”
Section: Enhanced Learning Experiencementioning
confidence: 99%